Supramolecular hydrogels constructed by red-light-responsive host–guest interactions for photo-controlled protein release in deep tissue1. Issue 38 (14th October 2015) - Wang, Dongsheng; Wagner, Manfred; Butt, Hans-Jürgen; Wu, Si
<x xml:space="preserve">Abstract</x> The red-light-responsive supramolecular interaction between tetra-ortho-methoxy-substituted azobenzene and β-cyclodextrin (β-CD) is demonstrated.